Combinatorial metabolic engineering of Pseudomonas putida KT2440 for efficient mineralization of 1,2,3-trichloropropane - Gong, Ting (Sci Rep, 2017)
An industrial waste, 1,2,3-trichloropropane (TCP), is toxic and extremely recalcitrant to biodegradation. To date, no natural TCP degraders able to mineralize TCP aerobically have been isolated. In this work, we engineered a biosafety Pseudomonas putida strain KT2440 for aerobic mineralization of TCP by implantation of a synthetic biodegradation pathway into the chromosome and further improved TCP mineralization using combinatorial engineering strategies. Initially, a synthetic pathway composed of haloalkane dehalogenase, haloalcohol dehalogenase and epoxide hydrolase was functionally assembled for the conversion of TCP into glycerol in P. putida KT2440. Then, the growth lag-phase of using glycerol as a growth precursor was eliminated by deleting the glpR gene, significantly enhancing the flux of carbon through the pathway. Subsequently, we improved the oxygen sequestering capacity of this strain through the heterologous expression of Vitreoscilla hemoglobin, which makes this strain able to mineralize TCP under oxygen-limited conditions. Lastly, we further improved intracellular energy charge (ATP/ADP ratio) and reducing power (NADPH/NADP(+) ratio) by deleting flagella-related genes in the genome of P. putida KT2440. The resulting strain (named KTU-TGVF) could efficiently utilize TCP as the sole source of carbon for growth. Degradation studies in a bioreactor highlight the value of this engineered strain for TCP bioremediation.